(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study presents a proposal for a practical activity to be carried out in the Experimental Behavior Analysis discipline as an alternative to the use of Sniffy and the students’ perception of it for their professional training. The activity consisted of installing a new response in a pet through the application of modeling and positive reinforcement procedures. Of the students enrolled in the discipline, 57.3% answered an anonymous questionnaire at the end of the semester that assessed the importance of the activity for professional training. Most students agreed that the proposed activity contributed to a clearer understanding of the concepts discussed in the course. The results of animal training and responses to the questionnaire indicated that the proposed activity can be an interesting, viable and efficient alternative for teaching basic principles of Behavior Analysis and knowledge and skills for research.